2016
DOI: 10.1021/jacs.6b06985
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeation versus Amyloidogenicity: A Multitechnique Study of Islet Amyloid Polypeptide Interaction with Model Membranes

Abstract: Islet amyloid polypeptide (IAPP) is responsible for cell depletion in the pancreatic islets of Langherans, and for multiple pathological consequences encountered by patients suffering from type 2 Diabetes Mellitus. We have examined the amyloidogenicity and cytotoxic mechanisms of this peptide by investigating model-membrane permeation and structural effects of fragments of the human IAPP and several rat IAPP mutants. In vitro experiments and molecular dynamics simulations reveal distinct physical segregation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 66 publications
7
56
0
Order By: Relevance
“…IAPP or amylin is a polypeptide pancreatic hormone formed by 37 amino acids, and it is synthetized, stored, and secreted with insulin by the PBC of the islets of Langerhans, although its synthesis has also been described in the gastric endocrine cells. Since it is cosecreted with insulin, it is to be expected that both hormones share the same stimuli for their release [ 114 ].…”
Section: Apoptosis Mediated By Endoplasmic Reticulum Stress: Rolementioning
confidence: 99%
“…IAPP or amylin is a polypeptide pancreatic hormone formed by 37 amino acids, and it is synthetized, stored, and secreted with insulin by the PBC of the islets of Langerhans, although its synthesis has also been described in the gastric endocrine cells. Since it is cosecreted with insulin, it is to be expected that both hormones share the same stimuli for their release [ 114 ].…”
Section: Apoptosis Mediated By Endoplasmic Reticulum Stress: Rolementioning
confidence: 99%
“…Nevertheless, simpler model systems can be implemented to extract selective structural information on a few lipid species and probe their potential interaction within the membrane or with proteins. Today, most of the simpler models focus on the main mammalian lipid phosphatidylcholine (PC) and some charged species such as phosphatidylserine (PS) or phosphatidylglycerol (PG) and sterols [15][16][17]. In this context, supported lipid bilayers (SLBs), are particularly relevant as they provide a stable flat structure and a highly tuneable composition, which make them optimal candidates for many different kinds of experiments involving surface-sensitive techniques [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of calcium ions has been shown to promote human-IAPP aggregation and membrane fragmentation via a carpet-like mechanism [94]. For more details on the biological properties of IAPP, we refer readers to studies reported in the literature [132138]. …”
Section: Protein Aggregation and Amyloid Formation In A Membrane Envimentioning
confidence: 99%